Strategi Komunikasi Lembaga Nazhir Wakaf Dalam Mensosialisasikan Program Wakaf Produktif Kepada Umat Islam - Faridatun Nadya Imaniah; Ahmad Asrof Fitri; Muhammad N. Abdurrazaq (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Nazir has a very important role in waqf, for this reason a good communication strategy is needed in socializing productive waqf programs to the community. The purpose of this research is to determine the communication strategy of the Nazir Waqf institution in socializing the waqf program to Muslims. This research uses a qualitative approach. Primary data is obtained from observation, interviews, notes or memos, and other official documents. Meanwhile, secondary data is obtained from scientific literature such as books, journal articles, theses, theses and websites. The results of this research show that the strategy carried out by the Pundi Amal Bhakti Ummat Foundation (PABU) is to identify communication targets, namely family, relatives, public figures, small groups such as the ta'lim assembly, arisan women, and communities. and the Muslim community. The choice of communication media, namely website, Facebook, and Instagram as communication media to socialize the waqf program, namely tabarru cards, and WhatsApp for telemarketing. In this case, for more effective communication, the PABU foundation plays the role of communicator who has jointed the waqf ambassador program, the program is organized by the Indonesian Waqf Board (BWI)